When cells lose water: Lessons from biophysics and molecular biology - Caramelo, Julio J.; Iusem, Norberto D. (Progress in biophysics and molecular biology, 2009)
Organisms living in deserts and anhydrobiotic species are useful models for unraveling mechanisms used to overcome water loss. In this context, late embryogenesis abundant (LEA) proteins and sugars have been extensively studied for protection against desiccation stress and desiccation tolerance. This article aims to reappraise the current understanding of these molecules by focusing on converging contributions from biochemistry, molecular biology, and the use of biophysical tools. Such tools have greatly advanced the field by uncovering intriguing aspects of protein 3-D structure, such as folding upon stress. We summarize the current research on cellular responses against water deficit at the molecular level, considering both plausible water loss–sensing mechanisms and genes governing signal transduction pathways. Finally, we propose models that could guide future experimentation, for example, by concentrating on the behavior of selected proteins in living cells.